Study on the section Trifoliolata DC. (Jasminum L. - Oleaceae Juss.) in Vietnam - Quang, Bui Hong; Phuong Anh, Tran Thi; Chinh, Vu Tien (Academia Journal of Biology, 2013)
Jasminum L. compcises about 200 species in the world including 5 sections: Jasminum Green, Alternifolia DC., Trifoliolata DC., Primulina Green and Unifoliolata DC. they distributed in tropical and subtropical in South East Asia, Europa, Australia and Africa. Section Trifoliolata DC. was published by De Candolle (1844) with the typus Jasminum didymum G. Forst. and characterized by leaves 3-foliolate, terminal leaflet slightly larger than or equal to lateral leaflets or sometimes, lateral leaflets reduced. There are about 10 species and 5 subspecies in this Section in the world. In Vietnam, there are 1 species and 2 subspecies in section Trifoliolata DC. recorded. In this paper to we introduced Jasminum sinense Hemsl. in sections Trifoliolata DC. as a new record for flora of Vietnam. This species is found in Ha Giang (Pho Bang) and has characteristic of Trifoliolata DC. section such leaves 3-foliolate. Jasminum sinense was closed to Jasminum brevilobum by lateral leaflets reduced, leaves and calyx pilose (different with Jasminum lanceolaria subsp. lanceolaria and Jasminum lanceolaria subsp. scortechinii by terminal leaflet slightly larger than or equal to lateral leaflets, leaves and calyx glabrous). But Jasminum sinense characterized by calyx lobes linear, 1-5 mm long. In this article, we introduce nomenclature, key to species, morphology and illustration, distribution and research specimen of three species of Trifoliolata DC. section (Jasminum L.) from Vietnam.